REDUCCIÓN DE LA DUREZA DEL AGUA A PARTIR DE ROCAS VOLCÁNICAS EN LECHOS DE ADSORCIÓN - Barahona Guilcapi, Fernanda Carolina (2019)
Natural waters have different levels of hardness due to the ease with which water dissolves various substances, hard water can affect health and generate operational damage at an industrial level, that is why the importance of its reduction. The purpose of this research is to reduce the hardness of natural water by using rocks from 4 volcanoes in the region: Chimborazo, Cotopaxi, Tungurahua and Reventador, these rock samples were evaluated as adsorption materials, of the total hardness of prepared adsorption beds 4 samples volcanic rock determining their effective size and performing individual chemical analysis (X-ray diffractogram and pH) to determine that mineralogical composition can affect its effectiveness. Initially water samples with pattern similar to natural water concentration were used, the results determined that each bed has a different adsorption capacity and which depends on the chemical composition of each rock. In addition, performance in reducing total hardness of two natural water from a well at the National University of Chimborazo and the slope of San Pablo (Guano) was evaluated; the results indicate that the volcanic rock of Chimborazo and Cotopaxi hold on average 34% hardness at its maximum efficiency point. In general rocks that have negative ΔpH and a higher content mineralogical phase andesine, anorthite and anorthoclase have higher adsorption capacity.